RELATIONSHIPS BETWEEN MORBIDITY FROM MPOX AND INTERNATIONAL TOURISM GLOBALLY DURING 2022-2024 EPIDEMICS - Alfonso J. Rodriguez-Morales; D. Katterine Bonilla-Aldana; Jaime A. Cardona-Ospina; Francisco Javier Membrillo de Novales; Ranji Sah (Brazilian Journal of Infectious Diseases, 2024)
Introduction: Multiple aspects of the Mpox epidemics during 2022-2024 have been explored, including clinical features, diagnostic aspects, therapies, and vaccines. However, socioeconomic aspects have been poorly assessed regarding the epidemiological associated factors. No studies have been published on the relationships between international tourism, measured as the annual number of arrivals per country, and the morbidity and mortality from Mpox. Methods: This study was conducted globally, encompassing data from 114 countries. We collected arrivals data from the World Tourism Organization (UNWTO) (2022/2023), the Tourism Statistics Database, and disease incidence data from the U.S. Centers for Disease Control (CDC) and the World Health Organization (WHO). We calculated incidence rates and assessed the annual variation of these variables. Non-linear regression models were then applied using Stata/MP® v.14.0. Results: The non-linear regression models revealed significant findings. The relationship between epidemiological factors and arrivals was found to be significant. During this epidemic, a higher number of cases was observed in countries with a higher number of arrivals (r2 = 0.2663; p < 0.0001), as well as the incidence rates (cases per 100,000 pop.) were higher also in those with a higher number of arrivals (r2 = 0.3039; p < 0.0001). We found 88 countries (42.7%) globally that have not reported cases of Mpox and 118 that have reported Mpox (57.2%); 25 of them (28.4%) are low-income countries, and 33 (37.5%) are from Africa. Discussion/conclusions: Our findings have interesting implications. They highlight the role of tourism and international travel, which may play a significant role in viral circulation for emerging diseases, such as Mpox. This is particularly relevant, considering that those countries with the highest income tourism should consider preparedness for other similar emerging conditions in the future. Despite the epidemics of 2022-2024, Mpox remains a neglected condition worldwide; with a resurgence in countries like the Democratic Republic of Congo in 2023-2024, high-income countries may experience new epidemics of Mpox. These findings underscore the urgent need for further studies on multiple epidemiological factors of Mpox. Keywords: Mpox, Epidemics, Tourism, Global, Surveillance. Conflicts of interest: There was no conflicts of interest. Ethics and financing: No financial support.